The threshold effect of market sentiment and inflation expectations on gold price. (August 2019) - Huang, Xiaoyong; Jia, Fei; Xu, Xiangyun; Yu shi,
Abstract: Although it is theoretically well established that market sentiment and inflation expectations influence gold price, limited research considers whether such effects vary depending upon the levels of market sentiment and inflation expectations. This paper addresses this gap by examining whether a threshold effect exists in the focal relationships. The results show that both market sentiment and inflation expectations significantly influence gold price only when their levels are beyond a certain threshold. However, market sentiment has a threshold effect only for the period after, rather than before, the global financial crisis. By contrast, a threshold effect is observed for inflation expectations in both before and after the global financial crisis periods. These findings advance our understanding of the effects of market sentiment and inflation expectations on gold price. Highlights: The paper examines the effects of market sentiment and inflation expectations on gold price. These effects are more important when the levels of financial market turbulence and inflation expectations are high. The threshold values with respect to market sentiment and inflation expectations are 17–19 and 2.3–2.5%, respectively. The threshold effect of market sentiment and inflation expectations varies between the before- and after- GFC periods.